Variational Approach for Solving the Ponds Seepage Problem - Fadhel, Fadhel S; Khayoon, Isam H (Al-Nahrain Journal of Science, 2018)
In this paper, the function of the pond’s seepage problem is derived using versional approach as especial case of generalized dam problem. In this problem the two dimensional cross section will produce problem with two free surfers which are evaluated as a part of the problem using simulating computer program.